Musik Internal dan Eksternal dalam Kesenian Randai - Rustiyanti, Sri (Institut Seni Indonesia Yogyakarta, 2014)
Kehidupan musik pada masyarakat Minangkabau tidak terlepas adanya peranan serta fungsi yang melekat pada kesenian Randai. Melalui pendekatan etnomusikologi, tulisan ini menelaah peranan musik internal dan eksternal dalam kesenian Randai. Kesenian ini menggunakan medium seni ganda atau kolektif karena didukung oleh beberapa cabang seni antara lain tari, musik, teater, sastra, dan rupa. Hasil penelitian menunjukkan bahwa musik iringan dalam Randai terbagi menjadi dua, yaitu musik internal dan musik eksternal. Musik internal adalah musik atau bunyi-bunyian yang berasal dari anggota tubuh manusia (penari), misalnya tepukan tangan, petik jari, tepuk dada, siulan, hentakan kaki ke tanah dan sebagainya, sedangkan musik eksternal adalah bunyi-bunyian atau suara yang berasal dari alat musik atau instrumen seperti talempong, gandang, saluang, dan rabab. The Role of Internal and External Music in the Arts of Randai. The musical life in Minangkabau society is inseparable from its roles and functions which attach to the arts of Randai. Through the ethnomusicology approach, this paper examines the role of internal and external music in the art of Randai. Considering its sustainability and amendment, the musicality is the identity of Minangkabau society so that the sustainability of the music can be run in accordance with the dynamics of society today. Among the types of arts in Minangkabau, Randai is an art form that uses multiple or collective art medium for it is supported by several branches of the arts, including dance, music, theater arts, literary arts, and fine arts. The results of this study is more focused on the art of music. Musical accompaniment in Randai is divided into two, namely internal and external music. The internal music is the music or the sounds that come from the human body (a dancer), for example, clapping, finger picking, patting the chest, whistling, stomping on the ground, and so on, while the external music is the sounds emanating from the tools of music or instruments, such as talempong, gandang, saluang, and rabab.